WEB SITE SEBAGAI SARANA PROMOSI DAN PEMESANAN JASA FOTOGRAFI ON LINE PADA AA PHOTOART MAGELANG - Rizky Adam Pratama; Cisilia Sundari; Muhammad Lutfi Mahasinul Akhlak (STMIK BINA PATRIA, 2021)
ABSTRACT The research has a goal to be able to create a Web Site as a means of promotion and ordering services for photography on line on AA Photoart. The research method used is the Waterfall system development model by Sommerville (2011). Consists of stages; Requirements Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and Maintenance. The design used in this research is DFD (Data Flow Diagram) and ERD modeling. System design refers to DFD and ERD modeling. The software used is the Windows operating system, Google Chrome or Opera web browser, XAMPP. PHP programming language is used in this study while the database used is MySQL. The results of this study are a Web Site as a means of promotion and ordering of photography services on line at AA Photo art Magelang which can make it easier to order photography services and simplify the process of scheduling, reporting and booking recap activities Keywords: Web, Waterfall, PHP, MySQL.